SOCIAL-PSYCHOLOGICAL SIGNIFICANCE OF COMMUNICATION IN STUDENTS IN A MODERN EDUCATIONAL ENVIRONMENT (Universal International Scientific Journal, 2026)
This article analyzes the importance of communication in the personal and social development of students. The impact of the communication process on the psychological stability of students, the effectiveness of learning, and social adaptation is scientifically highlighted. It also considers important aspects of forming an effective communication culture during student life.
Keywords: communication; student; interpersonal relationships